The Correlation of Families Role and the Quality of Life (QOL) of Diabetes Mellitus Patients - Noer Saudah; Enny Virda Yuniarti; Eka Ayu Wulandari (Journal of Ners and Midwifery, 2019)
Diabetes Mellitus is a disease that not only requires treatment but also lifestyle changes, so that often patients tend to despair with a long therapy program that will have an impact on the quality of life of patients. This study aimed to determine the correlation of family roles and the quality of life (QOL) of patients with Diabetes Mellitus. The design of this study was cross sectional analytic type. The population was all patients with diabetes mellitus and family on May-July 2018 at Dr Wahidin Sudiro Husodo General Hospital in Mojokerto as many as 96 people. The sample was 57 respondents taken by purposive sampling. The independent variable was family roles. The dependent variable was the quality of life. The instrument used a questionnaire of family roles and the quality of life. The data analysis used the Spearman statistical test. The results showed that 32 respondents (56.7%) or almost half of the respondents had enough family roles, almost all of the respondents or 38 respondents (66.7%) had a high quality of life of, and the results of p <Î± = 0.05 was 0.046 <0.05. There was a correlation between the role of family and the quality of life of patient with diabetes mellitus. The role of a good family can improve the quality of life of patients with Diabetes Mellitus. The better the role of the family, the higher the level of quality of life of the sufferer. Therefore the family can play a role in improving the quality of life Diabetes Mellitus sufferers.